The inextricable link between law and technology, from the TikTok case to the Meta-SIAE case (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The contribution first addresses a question of method, concerning the need for the jurist to interact with specialists from other branches of knowledge to adequately regulate technology. This method characterises what is referred to as digital constitutionalism: the regulation of new technologies must aim to protect the fundamental rights of individuals and, as far as necessary for this purpose, place limits on public and now especially private powers. The methodological theme is considered not in the abstract but with reference to two concrete cases: the one that concerned TikTok in the United States, which highlights possible repercussions on freedom of expression, for the demonstration of which the technological aspect is indispensable, and the one that concerned Meta and SIAE in Italy, concerning which the Council of State has already demonstrated considerable technological sensitivity.
Keywords: Regulation; technology; fundamental rights; judicial decisions; method